Methods of Estimating Risk Dealing with Declining Efficiency of Investment Project in Conditions of Statistic Uncertainty - N. P. Tikhomirov; T. M. Tikhomirova (Вестник Российского экономического университета имени Г. В. Плеханова)
The article analyzes different approaches to estimating risk of declining efficiency of investment projects that are recommended to practical use by academic literature. The author pointed to their subjectivity and high uncertainty of results. As an alternative we can consider approaches and methods of estimating risk of declining efficiency of the investment project as a difference between the expected by the project and risky values of its NPV defined by the law of this figure distribution. In this case the risky NPV assessment depending on the ratio to risk is either its average value in the field of existence limited from above by expected in the project value or any quantile located in the field of possible NPV values. The article presents substantiation of the standard law of NPV distribution as a complicated random value formed by a sum of random variables, i.e. features of finances flows by the project and discount. The author also analyses the approach to estimating dispersion of the NPV distribution law and risky values depending on its amount based on this figure expansion into the Tailor series with initial data showing average values and dispersion of its finance flows and discount.